2010
DOI: 10.1590/s1516-44462010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of Social Rhythm Metric in regular shift employees

Abstract: Objective: To analyze the psychometric properties of Brazilian version of Social Rhythm Metric-17 and to present the score algorithm in regular shift employees. Method: This is a cross-sectional study. The Social Rhythm Metric assess the regularity of daily life associated to changes in biological rhythms. The scale was applied, during nine days, to 145 employees, 27.6 % male and 72.4% female, ages between 18 and 60, mean = 36.1 (sd = 9.87). Mean values were compared using the Student's t-test for independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(28 reference statements)
0
5
1
Order By: Relevance
“…Another study from our group found that the regular activity of work days correlates with fewer minor psychiatric symptoms. 37 The results of the present study do not support an association between disrupted social rhythm and depressive symptoms. Certain methodological limitations might explain why we could not reproduce the previous findings.…”
Section: The Relevance Of Social Rhythm In Mood Dysfunctionscontrasting
confidence: 94%
“…Another study from our group found that the regular activity of work days correlates with fewer minor psychiatric symptoms. 37 The results of the present study do not support an association between disrupted social rhythm and depressive symptoms. Certain methodological limitations might explain why we could not reproduce the previous findings.…”
Section: The Relevance Of Social Rhythm In Mood Dysfunctionscontrasting
confidence: 94%
“…The disruption of the sleep–wake cycle is one of the most prevalent complaints in clinical practice. Sleep deprivation due to clinical and psychiatric conditions, as well as lifestyle, is endemic in modern life (Schimitt et al., 2010). Another important characteristic concerns interindividual differences in sleep allocation due to a time‐dependent behavior, the morningness–eveningness dimension (Horne & Ostberg, 1976).…”
mentioning
confidence: 99%
“…Zeitgeber is a German word coined by Jurgen Aschoff in the 1970s which loosely translates as "synchronizer" and is used to designate exogenous factors (light, exercises, food, social cues) that can synchronize biological rhythms (Schimitt, Zanetti, et al 2010). In our study, social zeitgebers were assessed using the Social Rhythm Metric, which scores the regularity of daily life from 0 to 7 over a period of 7 days by simply counting activities during this period (Schimitt, Zanetti, et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, social zeitgebers were assessed using the Social Rhythm Metric, which scores the regularity of daily life from 0 to 7 over a period of 7 days by simply counting activities during this period (Schimitt, Zanetti, et al 2010). The activity-rest rhythm and degree of exposure to the photic zeitgeber were analyzed using an ACT10 ® actigraph with a built-in thermistor and lux meter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation